Analisis Kalimat Efektif pada Teks Opini Tema “Pendidikan” dalam Website melintas.id Edisi 2025 sebagai Sumber Bacaan Edukasi - Tsalis Nafisaturrohmah; Zaskia Aida Nadzifah; Theresia Espara Giri; Keira Yasmin Aulia; Tsany Nur Hanifah; Asep Purwo Yudi Utomo; Septina Sulistyaningrum; Bivit Anggoro Prasetyo Nugroho (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Effective sentences are sentences that can convey messages or information in a concise, clear, and complete way, without changing the purpose and meaning. Utilizing effective sentences makes it easier for readers and listeners to grasp the meaning of the sentences conveyed. If you use ineffective sentences, the information you want to communicate will be difficult for readers or listeners to understand. Effective sentences can reduce unnecessary words, resulting in coherent sentences without presenting redundant information. This research aims to analyze the text of the use of ineffective sentences in opinion texts on the cross.id page regarding education and assess how well a sentence in an opinion text is able to convey the message of the author nicely. The method used in this writing uses a descriptive research method with a qualitative approach by applying, reading the and note-taking techniques. In analyzing the data, it uses literature study techniques sourced from scientific journals. While the data presentation technique uses tables. This research requires scientific journals and laptops. This study produces several ineffective sentences, witch was stand are classified into 3, namely 18 sentences of writing errors, 12 sentences of punctuation inaccuracy, and 1 sentence of capitalization inaccuracy. This study is useful as a guideline in writing effective sentences, besides that, recoders can pay more attention to the paper on effective sentences.